Application of CdTe/ZnSe Quantum Dots in In Vitro Imaging of Chicken Tissue and Embryo. (30th December 2014) - Moulick, Amitava; Blazkova, Iva; Milosavljevic, Vedran; Fohlerova, Zdenka; Hubalek, Jaromir; Kopel, Pavel; Vaculovicova, Marketa; Adam, Vojtech; Kizek, Rene
Abstract The present work is aimed to synthesize CdTe/ZnSe core/shell quantum dots (QDs) in an easy way and to explore the possibilities of its application in in vitro imaging of chicken tissue and embryo. The QDs were prepared using microwave irradiation with different temperatures, which is a very easy and less time‐consuming method. Subsequently, these QDs were characterized by spectrofluorimetry, Transmission Electron Microscopy, X‐ray fluorescence analysis and Dynamic Light Scattering measurement. A blueshifting of the emission was found when ZnSe was deposited on CdTe QDs. The QDs showed its fluorescence emission quantum yields up to 25%. They were applied into chicken embryos and breast muscle tissues to study their efficiency in in vitro imaging. All the QDs of different color were able to visualize in in vitro imaging. The highest fluorescence intensity was detected in the case of red QDs prepared at 100°C. The green and red QDs were possible to detect up to the depth of 3 and 4 mm of the tissue, respectively.